Behavioral intention towards mobile banking / Intan Syazwani Saleh - Saleh, Intan Syazwani (2017)
The advancement of technology and the raise of smart devices ownership in Malaysia has eventually increase the exploration of mobile banking services. Mobile banking has been first commercialize in Malaysia on 2005 and expected to growth. Despite the exponential growth, the mobile banking penetration rate is slow compared to online banking. Thus, this study was purposed to have insight on customer's behavioral intention. Therefore the factors and perceived risks are to identify in this study. Indepth, UTAUT2 model are use across this study to determine customer's behavioral intention. The model was tested in quantitative study conducted among young professionals in Klang Valley, Malaysia. The self-administered and email questionnaire with 384 valid selected results are indicated as following: (1) Impeding factors are found to be not the substantial barrier towards behavioral intention. (2) Perceived risk has moderate antecedent to behavioral intention and (3) Habit, price value and performance expectancy were found to be the most significant antecedents towards behavioral intention.